Unlocking Performance Through Motivation: The Impact of Job Transformation in the Ministry of Migrant Workers Protection - Iswari, Andina; Wati, Lela Nurlaela; Mulyanti, Rita Yuni (International Journal of Entrepreneurship and Sustainability Studies, 2025)
Job transformation is integral to bureaucratic reform initiatives aimed at enhancing employee efficiency and effectiveness. This study seeks to examine the function of work motivation as a mediator in the relationship between job transformation and employee performance at the Ministry of Indonesian Migrant Workers Protection (KP2MI). The research methodology employed causality with a sample of 251 KP2MI employees. Data analysis was conducted using a structural equation model employing a second-order confirmatory technique to test the hypotheses. The study's findings demonstrate that job transformation and work motivation significantly enhance employee performance. Work motivation mediates the impact of job transformation on employee performance, exerting a more significant effect than direct influence. This study suggests that work motivation significantly mediates the relationship between job transformation and employee performance. This study underscores the necessity of addressing job transformations that are both structural and psychological, particularly in enhancing employee motivation, which is crucial for increasing public sector performance. This study introduces an innovation in the realm of human resource management within the public sector, particularly at KP2MI. This study introduces a novel perspective that the efficacy of job transformation relies not only on structural or administrative factors but also on the capacity of these changes to foster employee motivation. The distinctive institutional framework of KP2MI, which has a specific purpose for the protection of migrant workers, renders this research pertinent and innovative in addressing the challenges posed by contemporary bureaucracy in government agencies that are adaptable and responsive to global employment issues.